A study to assess the knowledge and practice of nursing staff posted in postnatal ward about immediate care of newborn and breast feeding in selected hospital of Bhopal district, Madhya Pradesh - Khan, Amreen; Dohare, Pradeep K.; Melwani, Veena; Toppo, Manju; Lodha, Rama S.; Arshad, Shoaib (International Journal Of Community Medicine And Public Health, 2018)
Background: High rate of infancy deaths is largely attributed to very high share of neonatal deaths i.e 66% of infant deaths in 2007, in India. It can be largely attained by providing quality care to the newborn immediately after birth and Breast-feeding which is the standard way of feeding all infants. Objectives of the study were to assess the knowledge and practices of nurses regarding Immediate Care of Newborn and assess the knowledge of nurses of postnatal ward regarding Breast feeding. Methods: This was a hospital based cross-sectional study carried out in selected hospital of Bhopal district. 32 nurses involved in the immediate care of the newborn were identified. Data was collected about Immediate Care of Newborn and breast feeding. Analysis was done using MS Excel and EpiInfo-7. Results: 81.3% nurses knew how to prevent the new born from bleeding and 71.9% knew the correct dose of Vit K at birth. 78.1% put delivered baby on to mother’s abdomen, 84.4% dried and covered the baby correctly, 90.6% tied cord correctly and 96.9 weighted the baby. 75% said initiation should be done within first hour of birth. 90.6% said feeding should be done for more than 8 times a day and 87.5% believed hand washing should be done before every feed. 59.4% said Pre-lacteal feeding should not be given, 87.5% adhered to colostrum feeding. Conclusions: Nurses have knowledge about the immediate care of the newborn and breast feeding but there are some lacunas despite the continuous efforts of training. Much still needs to be done.